A candidate gene search for autism - Conroy, Judith (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2006)
This research involved a candidate gene search for autism in the Irish population. It sought to identify candidate genes based on information from linkage studies, reports of chromosomal abnormalities, animal studies and clinical observations, and previous reports of genetic association in other samples diagnosed with autism. Two replication studies were undertaken in genes from the serotonin system. Associations with the long and short promoter variants have been reported in samples with autism, as have no associations In the Irish population there was increased inheritance of the short promoter allele (p value = 0.03), in addition to a number of haplotypes across the gene. However a joint-analysis of the promoter allele highlights the possibility that this, and others may be false positive results. Another serotonin related gene, tryptophan hydroxylase 2, was also tested for association. Association with the A allele of marker rsl 1 17900 was found. Further replications in other samples are required to evaluate this genes contribution to the development of autism.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin